An improved form of smoothed particle hydrodynamics method for crack propagation simulation applied in rock mechanics - Yu, Shuyang; Ren, Xuhua; Zhang, Jixun; Wang, Haijun; Sun, Zhaohua (International journal of mining science and technology, 2021)
The simulation of crack propagation processes in rock engineering has been not only a research hot spot among scholars but also a challenge. Based on this background, a new numerical method named improved kernel of smoothed particle hydrodynamics (IKSPH) has been put forward. By improving the kernel function in the traditional smoothed particle hydrodynamics (SPH) method, the brittle fracture characteristics of the base particles are realized. The particle domain searching method (PDSM) has also been put forward to generate the arbitrary complex fissure networks. Three numerical examples are analyzed to validate the efficiency of IKSPH and PDSM, which can correctly reveal the morphology of wing crack and the laws of crack coalescence compared with previous experimental and numerical studies. Finally, a rock slope model with complex joints is numerically simulated and the progressive failure processes are exhibited, which indicates that the IKSPH method can be well applied to rock mechanics engineering. The research results showed that IKSPH method reduces the programming difficulties and avoids the traditional grid distortion, which can provide some references for the application of IKSPH to rock mechanics engineering and the understanding of rock fracture mechanisms.